Augmented Reality in E-Commerce: A Conceptual Exploration of Product Uncertainty and Customer Engagement - Hari Setiabudi Husni; Michelle Alicia Lynch; William Leo Walangitan; Aaron Kennedy (International Journal Science and Technology, 2025)
The growth of e-commerce has redefined consumer expectations, yet it continues to grapple with key limitations such as product uncertainty and insufficient customer engagement. Augmented Reality (AR) has emerged as a promising technological innovation, offering immersive product visualization that enhances consumer interaction and confidence in online shopping. This study provides a conceptual exploration of AR’s role in mitigating product-related uncertainty while simultaneously promoting deeper customer engagement within e-commerce platforms. Employing a systematic literature-based approach, the study synthesizes findings from peer-reviewed research across marketing, human-computer interaction, and information systems. The analysis identifies how AR reduces different dimensions of uncertainty—such as appearance, fit, and functional ambiguity—and outlines the psychological mechanisms, including trust formation and perceived interactivity, that mediate user responses. Furthermore, the study highlights the conditions under which AR fosters cognitive and emotional engagement, with implications for interface design and strategic technology adoption. This conceptual synthesis offers both theoretical insights and practical guidelines for e-commerce platforms considering AR integration. It also proposes a research agenda to empirically validate the conceptual model and expand understanding of AR’s long-term impact on consumer behavior.